Minimally permutated peptide analogs as internal standards for relative and absolute quantification of peptides and proteins - Winter, Dominic; Seidler, Jörg; Kugelstadt, Dominik; Derrer, Bianca; Kappes, Barbara; Lehmann, Wolf-Dieter (Proteomics, 2010)
A novel type of isobaric internal peptide standard for quantitative proteomics is described. The standard is a synthetic peptide derived from the target peptide by positional permutation of two amino acids. This type of internal standard is denominated minimally permutated peptide analog (MIPA). MIPA can be differentiated from their target analytes by LC-MS due to individual retention times and/or by MS/MS due to specific fragment ions. Both quantification methods are demonstrated using peptide mixtures of low and high complexity.